Meaningfulness in literary naming of Soccer Mascots within the Semiotic framework of Saussurean Structuralist Theory - Adebileje, Adebola Omolara (Journal of English Language and Literature (ISSN: 2368-2132), 2016)
This paper examines some randomly selected sport mascots from lists of All African Games and African Cup of Nations events from 2000 to 2013. Selected mascots and their names are subjected to semiotic analysis premised on the Saussurean structuralist theory. Surface structure signs and symbols are analysed to determine their deep significances through the medium of syntagmatic analysis.